Elimination of carbapenem resistant Klebsiella pneumoniae in water by UV-C, UV-C/persulfate and UV-C/H2O2. Evaluation of response to antibiotic, residual effect of the processes and removal of resistance gene. Issue 1 (February 2020) - Serna-Galvis, Efraím A.; Salazar-Ospina, Lorena; Jiménez, J. Natalia; Pino, Nancy J.; Torres-Palma, Ricardo A.
Abstract: This work studies the individual application of UV-C, UV-C/persulfate and UV-C/H2 O2 to inactivate Klebsiella pneumoniae resistant to carbapenem antibiotics (CR-Kp, one priority pathogen due to its fast propagation and capacity to resist last resort antibiotics). Herein, secondary effluent of municipal wastewater treatment plant and deionized water previously inoculated with CR-Kp were submitted to the three processes. Bacteria inactivation, effect on the resistance during treatments, residual action of processes, microorganism regrowth ability and elimination of the gene responsible for resistance were evaluated. A fast and total microorganism removal was found in the three processes in both waters: municipal wastewater (at 180 s) and deionized water (at 60 s). The cultivability evaluation in selective medium containing carbapenems indicated that the response to antibiotic of bacteria treated by UV-C/PS or UV-C/H2 O2 is higher than the submitted to UV-C alone. The analysis of processes residual effect showed that persulfate anion continued the inactivating action on the bacteria when light was turned off. In deionized water, after 24 h of treatments cessation, the microorganism showed no regrowth, evidencing that 60 s of processes action was enough time to induce irreparable damages on the resistant bacteria. Additionally, the resistance gene ( bla KPC-3) evolution showed that the processes must be extended more time than required for bacteria inactivation to ensure its elimination. Also, it was observed that the resistance gene removal rate followed the order: UV-C/PS > UV-C/H2 O2  > UV-C. These results remark the superior potential of UV-C plus persulfate in the removal of CR-Kp in waters.